Hansal aur gretal - Akhter Saleem (Ferozesons; Pakistan, 2012)
Hansel Aur Gretel is a classic fairy tale of two siblings who outwit a wicked witch, overcoming challenges and showcasing the power of bravery and resourcefulness.